The relationship between impact force, neck strength, and neurocognitive performance in soccer heading in adolescent females - Gutierrez, G. M.; Conte, C.; Lightbourne, K. (Pediatric Exercise Science, 2014)
Head impacts are common in contact sports, but only recently has there been a rising awareness of the effects of subconcussive impacts in adolescent athletes. A better understanding of how to attenuate head impacts is needed and therefore, this study investigated the relationship between neck strength, impact, and neurocognitive function in an acute bout of soccer heading in a sample of female high school varsity soccer players. Seventeen participants completed the ImPACT neurocognitive test and had their isometric neck strength tested (flexion, extension, and bilateral flexion) before heading drills. Each participant was outfitted with custom headgear with timing switches and a three-dimensional accelerometer affixed to the back of the head, which allowed for measurement of impact during heading. Participants performed a series of 15 directional headers, including 5 forward, 5 left and 5 right headers in a random order, then completed the ImPACT test again. Neurocognitive tests revealed no significant changes following heading. However, there were statistically significant, moderate, negative correlations (r = -0.500:-0.757, p < .05) between neck strength and resultant header acceleration, indicating that those with weaker necks sustained greater impacts. This suggests neck strengthening may be an important component of any head injury prevention/reduction program.